The form of legislation and the rule of law - Cormacain, Ronan (London : Hart Publishing, 2022)
What does the rule of law mean, in practical terms, for the way that legislation is prepared, drafted and presented? It is a cornerstone of the UK legal order and requires certain things from the legal system, such as that the law must be intelligible, predictable and accessible. This book examines what those requirements mean for the form that legislation must take. Using the rule of law as the starting point, the author uses deductive reasoning to determine what flows from this in terms of the form of legislation. Each element of the rule of law is analysed to establish principles about the form that legislation ought to take, and the book examines how each principle can be given concrete effect. The originality lies in the nexus between the rule of law and the form of legislation. Much has been written about the nature and content of the rule of law, but relatively little has been devoted to legisprudence, the theory and practice of legislation. This book now draws these two subjects together in a detailed and innovative way..
1. Introduction --2. Accessibility of Legislation --3. Prospectivity of Legislation --4. Predictability of Legislation --5. Intelligibility --6. Law not Discretion --7. Equality before the Law --8. Conclusion.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Keywords: Constitutional law; Law -- Legal profession -- United Kingdom; Legislation